Effectiveness of Efforts to Eradicate Land Mafia in Cirebon City - Ridwan, Nanang; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2025)
Land mafia is a serious problem that can harm society and the state. As a serious problem, the law, which is a state instrument in national land management that is mandated to be able to eradicate land mafia, has not been optimally implemented. This is proven by the increasing number of land mafia cases, including in the Cirebon City area. This thesis research aims to determine and analyze the implementation of land mafia eradication efforts in the Cirebon City Area at this time and to determine and analyze the obstacles and solutions in implementing land mafia eradication efforts in the Cirebon City Area at this time. The type of legal research used is analytical descriptive. In this non-doctrinal legal research, law is conceptualized as a manifestation of the symbolic meanings of social actors as seen in the interactions between them. That the real reality of life does not exist in the empirical world which is also the world of observation, does not appear in the form of objectively patterned and structured behavior (let alone normative) and therefore can be measured to produce quantitative data. Based on the research conducted, it was found that the implementation of efforts to eradicate land mafia in the Cirebon City area is currently not optimal, this is because...the absence of regulations regarding the criminal law enforcement process in the Technical Instructions of the Ministry of Agrarian Affairs and Land Affairs Number 01/JUKNIS/D.VII/2018 concerning the Prevention and Eradication of Land Mafia. So that the Technical Instructions of the Ministry of Agrarian Affairs and Land Affairs Number 01/JUKNIS/D.VII/2018 concerning the Prevention and Eradication of Land Mafia only regulate the implementation of handling land mafia cases with an administrative approach, this results in a lack of severe sanctions to create a deterrent effect for land mafia perpetrators inCirebon City. Suggestions that can be given in this thesis are bFor the public, it is necessary to understand the importance of proper management and storage of land ownership certificate documents, and for the government, it is necessary to emphasize the mechanism for implementing criminal sanctions in the Technical Instructions of the Ministry of Agrarian Affairs and Land Affairs Number 01/JUKNIS/D.VII/2018 concerning the Prevention and Eradication of Land Mafia to create a deterrent effect for land mafia perpetrators.